Implementation of Certainty Factor Method for Identification of Pest Types on Dendrobium Based on Expert Systems - Muhammad Innuddin; Hairani Hairani; Ida Putu Andika (Sistemasi: Jurnal Sistem Informasi, 2023)
Orchid is an ornamental plant that has high aesthetic value with a variety of attractive colors on its flowers and has high economic value. One of the problems in the cultivation of orchids is the problem of pests that can inhibit growth and reduce the aesthetics of orchid plants. Not only that, the shortage of orchid plant experts can be a trigger for delays in identifying the types of pests on orchids, resulting in poor growth quality and even crop failure. Early identification is needed so that handling is fast so that the quality of growth is good. The solution offered by this research is the implementation of the certainty factor method for identifying web-based types of pests on dendrobium orchids. The stages of this research consist of knowledge acquisition, knowledge modeling, implementation, and accuracy testing. Based on the test results of 32 data, the certainty factor method can identify exactly 29 data and the rest are identified incorrectly, resulting in an accuracy of 90.6%. Thus, the certainty factor method can be used to identify the type of pest on orchids because it has very good accuracy.